Deliberative reading in Ahwa Al Shaam poem to the poet Badawi Al Jabal - باسم حسن عباس; محمد اسماعيل بصل; تيسير سليمان جريكوس (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This study is an attempt to discover the indications inside the language that is verified in the poetry text in the light of the deliberative reading ,and through it this study tries to answer many questions such as:who speaks?about what he/she speaks?what do we do when we speak?what is the meaning of the speaking that we say? This study aims to say that we can use the poetry speech from deliberative side to discover its hidden things and its indications and the intentions of its sender, and his/her ability in convincing and effect. Key words: reading, deliberative , Badawi Al Jabal